2020
DOI: 10.3390/educsci10090239
|View full text |Cite
|
Sign up to set email alerts
|

Makey Makey as an Interactive Robotic Tool for High School Students’ Learning in Multicultural Contexts

Abstract: Information and communication technologies (ICT) are immersed in the teaching and learning processes. Specifically, educational robotics is a technology with great projection in learning spaces. This educational technology has revealed great potential in educational processes in the scientific literature. In this study, the Makey Makey device has been used to carry out a methodological contrast at the instructional level. The objective of this study is to verify if the use of the Makey Makey robotic device inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
0
19
0
1
Order By: Relevance
“…As has been possible to verify after the state of the matter presented, current teaching is conditioned by the incidence of technology [59] that has reported a set of potentialities, from which the teaching and learning processes have benefited [60]. Until relatively recently, teachers did not fully support the use of ICT in instructional actions, since to some extent, the level of digital competence of teachers determines how they will be able [61] to apply with ease and confidence a training process mediated by educational technology [62] and that allows the implementation of active and emerging methodologies [63].…”
Section: Justification and Research Objectivementioning
confidence: 99%
“…As has been possible to verify after the state of the matter presented, current teaching is conditioned by the incidence of technology [59] that has reported a set of potentialities, from which the teaching and learning processes have benefited [60]. Until relatively recently, teachers did not fully support the use of ICT in instructional actions, since to some extent, the level of digital competence of teachers determines how they will be able [61] to apply with ease and confidence a training process mediated by educational technology [62] and that allows the implementation of active and emerging methodologies [63].…”
Section: Justification and Research Objectivementioning
confidence: 99%
“…From this perspective, the most current approaches to the development of teacher competence in technology integration have made technological knowledge alone less important. In this case, they have focused on the essential connections between technology, pedagogy and content knowledge (TPACK) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a qualitative study showed that robotic education at the tertiary level had positive effects on learner's intrinsic motivation (Apiola & Tedre, 2013). Moreover, robotic education correlates positively with motivation (Aris & Orcos, 2019) and affects the motivation of high school students positively (Marín-Marín, Costa, Moreno-Guerrero, & López-Belmonte, 2020). Moreover, it increases motivation, devotion, and enjoyment at the primary level (Sáez-López, Sevillano-García, & Vazquez-Cano, 2019).…”
Section: Discussionmentioning
confidence: 98%